Performance Enhancement of a Hybrid Solar Still/Photovoltaic System with Mirror Reflectors, Automatic Water Cooling, and Feed Water Preheating - Yadav, P.; Singh, B.; Subedar; Kumar, S.; Singh, S. P.; Singh, S. K. (Russian physics journal, 2024)
The hybrid system integrating a solar photovoltaic (PV) module and a passive single-slope solar still (PSSSS) has been designed and tested. The PV module, equipped with mirror reflectors and automatic water cooling, is aimed to enhance the solar radiation input and reduce the module surface temperature. Preheated feedwater maintained a constant basin water level in the PSSSS. April and May 2022 experiments revealed a 12.5% daily average efficiency for the PV module in the hybrid setup, marking a 21.6% improvement over conventional photovoltaic module. The PSSSS in the hybrid configuration yielded 25% more distilled water (2.7 L/day) than a standalone solar still. The hybrid system achieved maximum overall efficiencies of approximately 61.5% and 58.5% in April and May 2022, respectively.